Cultural representative subcorpus: the importance of preserving national cultural and cognitive units in the digital space - Utebayeva, Э.Ә.; Koishygulova, Л.Р.; Nustaeva, А.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article discusses the structure and significance of the cultural-representative subcorpus and its role in preserving and presenting national cultural and linguistic units in the digital space. The electronic National Corpus of the Kazakh Language is an important and reliable informational resource for the development of the national language and culture. The cultural-representative subcorpus within the corpus is considered not only as a tool for a deeper understanding of the ethnocultural development of the Kazakh ethnicity, its spiritual and material values, ethnographic and cultural-cognitive concepts, but also as an important cognitive mechanism reflecting the unifying function of the linguistic heritage. The aim of the article is, based on the scientific foundations of Kazakh ethnolinguistics, to define the creation of the cultural-representative subcorpus within the National Corpus of the Kazakh Language (NCKL) and to determine ways to study and preserve national culture, traditions, historical and social aspects through a digital platform that accumulates linguistic and cultural values of the Kazakh language. The composition, structure, and application methods of the subcorpus are also presented, and its importance in education and scientific research is demonstrated. The research object is the cultural-representative subcorpus within NCKL and the linguistic and cultural materials of Kazakh ethnolinguistics collected therein.